2015
DOI: 10.1016/j.biomaterials.2015.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Role of integrin subunits in mesenchymal stem cell differentiation and osteoblast maturation on graphitic carbon-coated microstructured surfaces

Abstract: Surface roughness, topography, chemistry, and energy promote osteoblast differentiation and increase osteogenic local factor production in vitro and bone-to-implant contact in vivo, but the mechanisms involved are not well understood. Knockdown of integrin heterodimer alpha2beta1 (α2β1) blocks the osteogenic effects of the surface, suggesting signaling by this integrin homodimer is required. The purpose of the present study was to separate effects of surface chemistry and surface structure on integrin expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 68 publications
(61 reference statements)
2
54
0
4
Order By: Relevance
“…The pattern of integrin expression is similar to that reported by other authors studying the effect of the microtopography; the cells exhibited an increase in the expression of α1, α2, and β1 mRNA on the surface with the highest differentiation, while α5 showed an opposite behavior. In this work, it was observed that in all cases, the SLA surfaces (coated or uncoated) presented the lowest attachment and cell number, but the highest gene and protein expression associated with osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The pattern of integrin expression is similar to that reported by other authors studying the effect of the microtopography; the cells exhibited an increase in the expression of α1, α2, and β1 mRNA on the surface with the highest differentiation, while α5 showed an opposite behavior. In this work, it was observed that in all cases, the SLA surfaces (coated or uncoated) presented the lowest attachment and cell number, but the highest gene and protein expression associated with osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 88%
“…In this work, it was observed that in all cases, the SLA surfaces (coated or uncoated) presented the lowest attachment and cell number, but the highest gene and protein expression associated with osteogenic differentiation. Previous studies have shown that common integrin subunits are upregulated by the surface roughness in biomaterials with different chemistries; expression of α1, α2, and β1 were higher on rough titanium than on smooth surfaces. Moreover, it has been demonstrated that integrin expression is modulated when cells are grown on Ti‐based surfaces with different roughness, and control of integrin expression is partially regulated by Wnt signaling .…”
Section: Discussionmentioning
confidence: 88%
“…41 In particular, β1 integrin interacting with FN is known to play a major role in roughness recognition on graphitic carboncoated substrates. 42 In this study, GPS was coated with FN to increase hNSC adhesion, and thus 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 hNSCs ( Figure 5B). qRT-PCR analysis for FAK and vinculin revealed that the gene expression levels of those focal adhesion proteins in hNSCs grown on the GPS with 5-µm groove width was remarkably downregulated by the treatments with β1 integrin antibodies, blebbistatin, and Y27632, compared with no treatment ( Figure 5C).…”
Section: Mechanisms Of Enhanced Differentiation Of Hnscs By Hierarchimentioning
confidence: 98%
“…These discoveries led us to further attempt to delineate effects of surface nanotopography and wettability Olivares-Navarrete, Rodil, et al 2015).…”
Section: Surface Roughnessmentioning
confidence: 99%
“…To more clearly determine the specific contributions of topography and chemistry, we compared responses of human MSCs and MG63 cells to smooth and microtextured titanium and to the same surfaces coated with a nanofilm of graphitic carbon (Olivares-Navarrete, Rodil, et al 2015). Osteogenic differentiation and maturation were enhanced on rougher surfaces, regardless of the chemistry.…”
Section: Cell Morphology and Integrin Signalingmentioning
confidence: 99%